Penjaminan Mutu pada Learning Outcomes Pondok Pesantren - Khoirun Nisa' (Universitas Hasyim Asy'ari (UNHASY) Tebuireng Jombang, 2019)
The seminary is the oldest Islamic institution in Indonesia. So in this case there needs to be development and renewal, in order that the boarding school was not outdated. In an effort to improve the quality and characteristics of comprehensive description is from the field or service that shows in the ability to satisfy the needs of the expected or implied. In the context of education, the notion of quality includes input, process, and output of education. The motion of national development or challenge nowadays has been on a